1995
DOI: 10.1172/jci118114
|View full text |Cite
|
Sign up to set email alerts
|

Zonula occludens toxin modulates tight junctions through protein kinase C-dependent actin reorganization, in vitro.

Abstract: The intracellular signaling involved in the mechanism of action of zonula occludens toxin (ZOT) was studied using several in vitro and ex vivo models. ZOT showed a selective effect among various cell lines tested, suggesting that it may interact with a specific receptor, whose surface expression on various cells differs. When tested in IEC6 cell monolayers, ZOT-containing supernatants induced a redistribution of the F-actin cytoskeleton. Similar results were obtained with rabbit ileal mucosa, where the reorgan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
264
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 316 publications
(273 citation statements)
references
References 55 publications
9
264
0
Order By: Relevance
“…We observed in this paper that endothelial PKC activation is clearly involved, although to a lesser extent than calcium, in lymphocyte transmigration. PKC activation is correlated with tight junction regulation, via a mechanism involving actin reorganization (39). The role of PKCs during transendothelial migration may be due to their ability to mediate ICAM-1-coupled cytoskeletal rearrangements.…”
Section: Discussionmentioning
confidence: 99%
“…We observed in this paper that endothelial PKC activation is clearly involved, although to a lesser extent than calcium, in lymphocyte transmigration. PKC activation is correlated with tight junction regulation, via a mechanism involving actin reorganization (39). The role of PKCs during transendothelial migration may be due to their ability to mediate ICAM-1-coupled cytoskeletal rearrangements.…”
Section: Discussionmentioning
confidence: 99%
“…We have recently demonstrated that Zot activates a complex intracellular cascade of events that regulate intestinal permeability (9). Zot induces a dose-and time-dependent PKC␣-related polymerization of actin filaments strategically localized to regulate the paracellular pathway (9).…”
Section: Discussionmentioning
confidence: 99%
“…Zot (a) is not cytotoxic and does not affect the viability of the intestinal epithelium ex vivo (7,9); (b) fails to completely abolish the intestinal transepithelial resistance (7,9, and present paper), (c) interacts with a specific intestinal receptor whose regional distribution within the intestine varies (10), (d) is not effective in the large intestine where the presence of the colonic microflora could be potentially harmful if the mucosal barrier was compromised (10 and present paper), (e) does not induce acute systemic side-effects (for at least 80-90 h) when orally administered (present paper), and (f) induces a reversible increase of tissue permeability (7,9, and present paper). Our results demonstrate that coadministration of Zot with biologically active ingredients enhances intestinal absorption of the active molecule, and that this enhancement is effective for both relatively small (insulin, 5733 D) and large molecules (IgG, 140-160 kD).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it is well accepted that tj are dynamic structures, surprisingly little is known about their regulation. The discovery of zonula occludens toxin (Zot), a protein elaborated by Vibrio cholerae (18) and of its receptor (19), has shed some light on the intricate mechanisms involved in the modulation of the intestinal paracellular pathway (20) and led us to the discovery of its eukaryotic counterpart zonulin (21). This protein is involved in the innate immunity of the gut (3) and, when inappropriately up-regulated, appears to play a key role in the increased intestinal permeability and pathogenesis of autoimmune diseases such as CD (22).…”
mentioning
confidence: 99%